Pyrazole-tethered heteroditopic ligands and their transition metal complexes: synthesis, structure, and reactivity - Mukherjee, Anuradha; Subramanyam, U.; Puranik, Vedavati G.; Mohandas, T. P.; Sarkar, A. (European Journal of Inorganic Chemistry, 2005)
Various pyrazole-based PN (2a-c) and N,N (3a-b) ligands have been synthesized. Using representative ligands, Ni-II, Co-II, Cu-II, and Cu-I complexes have been prepared and structurally characterized by crystallography. During complexation of Co-II and Cu-II salts, the phosphane part of the PN ligand oxidized to phosphane oxide. For N,N donor ligands, a dimeric chloro-bridged Ni-III complex was obtained. Ni-II complex 4 is an active catalyst for ethylene oligomerization. ((c) Wiley-VCH Verlag GmbH & Co. KGaA, 69451 Weinheirn, Germany, 2005).
Keywords: cobalt; Copper; hemilabile ligands; Nickel; oligomerization; Pyrazole

Synthesis, structure, electrochemistry and ROMP-activity of new ferrocenyl analog of Grubbs' metathesis catalyst - Maishal, T. K.; Mondal, Biplab; Puranik, Vedavati G.; Wadgaonkar, P. P.; Lahiri, Goutam Kumar; Sarkar, A. (Journal of Organometallic Chemistry, 2005)
Treatment of [(PCy3)(2)Cl2Ru=CH-Ph] (1) with vinylferrocene 1 and 1-ferrocenyl-1,3-butadiene 2 yielded solid products. These new complexes were characterized by H-1 NMR, P-31 NMR and C-13 NMR spectroscopy. X-ray crystal structures of both the complexes have been solved. The crystal structure of II confirmed the assigned structure and revealed existence of two sets of intermolecular C-H-Cl(M) type interactions, viz. (Ru)Cl-H-C(ferrocene) and (Ru)Cl-H-CHCl2. The air-stable, dark solid II is all efficient catalyst for ring-opening metathesis polymerization (ROMP) of cyclopentene, norbornene and cycloocta-1,5-diene. Electrochemical behavior of the complexes clearly reflects electronic communication between two metal centers. (C) 2004 Elsevier B.V. All rights reserved.
Keywords: Electrochemistry; ferrocene; Metathesis; non-covalent interactions; ring-opening metathesis polymerization; ruthenium carbene

Flufenoxuron, an acylurea insect growth regulator, alters development of Tribolium castaneum (Herbst) (Coleoptera :tenebrionidae) by modulating levels of chitin, soluble protein content, and HSP70 and p34(cdc2) in the larval tissues - Salokhe, S.; Sarkar, A.; Kulkarni, A.; Mukherjee, Samindra N.; Pal, J. K. (Pesticide Biochemistry and Physiology, 2006)
The effect of sublethal concentrations, 0.00141% (LC20), 0.00251% (LC30), and 0.0036% (LC40) of a dispersible formulation of an acylurea insect growth regulator, flufenoxuron (Cascade) on certain biochemical parameters in the larvae of Tribolium castaneum was investigated. When neonates were fed on diet treated with sublethal concentrations for 24 It, it was observed that at all concentrations tested, there was a significant reduction in chitin content on the 15th day of development. Total soluble protein content at LC20 and LC30 decreased with increasing age of the larvae. At LC20 and LC40 concentrations there was a progressive increase in the protein: chitin ratio as a function of increase in age of the larvae. SDS-PAGE analysis of the larval tissue extracts indicated gross quantitative changes in some of the protein bands (MW 50-97 kDa). Western blot analysis revealed significant increase in the level of HSP70 in the extracts of larvae fed on LC30 treated diet, on the 7th and 10th day of development in the decreasing order. Conversely, a significant decrease in the hyper-phosphorylated form of p34(cdc2) kinase due to flufenoxuron treatment indicating modulation of cell cycle regulation was observed. Thus, sublethal concentrations of flufenoxuron alter expression of developmentally regulated proteins, HSP70 and p34(cdc2) and chitin formation in a stage-specific manner thereby resulting developmental abnormalities in T castaneum. (c) 2005 Elsevier Inc. All rights reserved.
Keywords: chitin; Development; flufenoxuron; HSP70; p34(cdc2); phosphotyrosine; sublethal effects; total soluble proteins; Tribolium castaneum